Spatial Regression in the Presence of a Hierarchical Transportation Network: Application to Land Price Analysis - Murakami, Daisuke; Seya, Hajime (Frontiers in Sustainable Cities, 2022)
Transportation networks have a hierarchical structure, and the spatial scale of their impact on urban growth differs depending on the hierarchy. However, in empirical analyses of the impacts that transportation has on land use and prices, such hierarchy is often examined using dummy variables, and the network dependence and heterogeneity of impacts are often ignored. Thus, this study develops a spatial regression method that considers not only spatial dependence, but also network dependence within a hierarchical transportation network. This method was developed by extending the random effects eigenvector spatial filtering approach. Subsequently, it was applied to a pre-existing analysis that focused on the impacts that high-speed rail (HSR) had on residential land prices in Japan over the last 30 years. The results of the analysis suggested that HSR lines had hierarchical effects on residential land prices. The results also provide interesting insight into the ongoing problem of Japanese urban hierarchy; that is, the excessive concentration of population and industry in the Tokyo metropolitan area.